Review of Recent Patents on Anaerobic Digester Gas for Fuel Cell Applications - Warlick, Billy; Diaz, Christian; S. Vasconcelos, Paulo; Crespo, Cristina; Aboy, Mateo (Recent Patents on Engineering, 2015)
This article reviews recent patents pertaining to the technological achievements and shortcomings of anaerobic digestion technology that optimize biogas production for use in fuel cells. The technical field of anaerobic digestion is well understood and known as an effective means to safely process organic waste and produce useful byproducts including compost, methane and hydrogen gas. While fuel cells have proven effective in producing power from biogas, including methanol and hydrogen derived thereof, the process of doing so with anaerobic digester gas (ADG) remains costly and more complex compared to sourcing fuel from natural gas or pure methanol. This paper reviews recent advancements in anaerobic digestion technology that optimize gas production for use in fuel cells, including improved anaerobic digestion processes, establishing more efficient digester designs, lowering operational costs, and purifying biogas to better suit fuel cells. A few developing niche applications are also discussed. A patent search revealed only 59 US patents that focus specifically on the use of anaerobic digestion to power fuel cells, 32% of which were published in the last five years. Similarly, 77 US patent application publications were found using the same search with 70% of those published in the last five years. It appears that while advancements are being made, growth of the technology is slow and widespread use of fuel cells remains more of a goal than a current reality. While much advancement is based upon improvements of older anaerobic digester technology, some patent applications are directed to lesser-known arts such as microbial fuel cells.
Keywords: microorganism